Sheikh Burhanuddin's Cultural Da'wah System in Minangkabau - Nazirman Nazirman; Saharman Saharman; Abdul Manan Sihombing (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2021)
This discourse describes Syekh Burhanuddin's cultural da'wah system in Minangkabau as one of the classical da'wah role models that have taken root and preserved to this day. This study aims to reveal the structure and system of da'wah built by Syekh Burhanuddin through a qualitative research method with a historical, descriptive analysis approach. The data collection technique used snowball sampling by taking locations in Ulakan Padang Pariaman, Kenagarian Puluik-Puluik and Kapujan Bayang Pesisir Selatan, Kenagarian Agarng Payung Sekaki, Solok district, and Koto Tangah, Padang City. The research shows that Sheikh Burhanuddin's cultural da'wah system is integrated and has a multi-level da'wah pattern in the da'wah network known as the seven pillars of syattariyyah da'wah, including: Syekh Tuo Koto Tuo, Tuanku Qadi in Lubuk Ipuh, Angku Qadi seven Koto (Toboh Karambia), Tuanku Qadhi Koto Gadang, Ampu Sarak in Sintuak, Tuanku Qadi Toboh Gadang, and Tuanku Qadi in Pakandangan. The seven pillars are representative reflections of the modeling of cultural da'wah in Minangkabau.